COMP-Ang-1 improves glucose uptake in db/db mice with Type 2 Diabetes - Baum, Petra; Paeschke, Sabine; Klöting-Blüher, Nora; Blüher, Matthias; Kern, Matthias; Serke, Heike; Nowicki, Marcin; Kosacka-Esmailpour, Joanna (Hormone and metabolic research, 2020)
Cartilage oligomeric matrix protein (COMP)-Angiopoietin-1 is a potent angiopoietin-1 (Ang-1) variant that possesses therapeutic potential in angiogenesis and vascular endothelial dysfunction. Noteworthy, we have shown that COMP-Ang-1 improves hyperglycemia and neuroregeneration in ob/ob mice. However, the mechanism of the antidiabetic effect of COMP-Ang-1 is completely unknown. Therefore, we elucidated the diabetes protective molecular mechanisms of COMP-Ang-1 in diabetic db/db mouse model. COMP-Ang-1 (0.5 ng/g body weight) or aqueous NaCl solution was injected intraperitoneally per day in 21 consecutive days into 3-month old, male db/db mice (n=10 per group). Blood glucose and HbA1c levels were determined at baseline and 21 days after COMP-Ang-1 or NaCl treatment. The effect of COMP-Ang-1 on glucose uptake was investigated by euglycemic-hyperinsulinemic clamp studies and key genes of glucose metabolism were studied by Western blot analysis. Our findings indicate that COMP-Ang-1 improves glucose metabolism in a tissue specific manner by regulating HIF-1α transcriptional genes of GLUT-1 expression.
Gesehen am 22.12.2025